The Complexity Problem on the Law Enforcement by Indonesian Police Agency during the COVID-19 Pandemic - Dwi Putri Hardiani; Nyoman Serikat Putra Jaya (Unram Law Review, 2020)
In Indonesia, the COVID-19 pandemic can be a fundamental concern if it is not able to overcome its impact. This pandemic considered to be very influential in affecting and disturbing several fundamental aspects of a country, such as health, economic, legal aspect, defense and security, and etc. This study examined the complexity problem of law enforcement by the police officer during the COVID-19 pandemic. The method of this researchusesnormative legal research by prioritizing secondary data that analyzed descriptive qualitative analysis techniques. The results of this study indicate that the police are referred to the law that lives in the community because of the work of the police plays an important role in maintaining the security and defense of the community, the law enforcement, as well as providing protection, protection, and services to the community. This has placed the police in dealing with various dynamics of social changing including the current COVID-19 pandemic. However, the problem with police law enforcement in the current COVID-19 pandemic arises from the implementation of Large-Scale Social Restrictions (PSBB) policy, the complexity problem in law enforcement on PSBB, and the choice to the possible solutions.